A neglected Meaning for SKEUOS in 1 Thessalonians 4.4 - Whitton, J. (New Testament studies, 1982)
Discussion of the meaning of σκєυ>ος in 1 Thess. 4. 4 has traditionally centred on two possible connotations, ‘body’ and ‘wife’ (cf. respectively, B. Rigaux, Les Epitres aux Thessaloniciens, 1956, pp. 503–7; E. Best, The First and Second Epistles to the Thessalonians, 1972, pp. 160–5).